Overfishing and sea warming drive the collapse of Paracentrotus lividus - Andrea Toso; Francesca Necci; Alessandra Martines; Roberta Lacorte; Yann Toso; Paola Gianguzza; Alan Deidun; Nicola Ungaro; Gaetano Costantino; Marianna Caforio; Cosimo Gaspare Giannuzzi; Francesco Marco D’Onghia; et al. (Scientific Reports)
Abstract As a seafood delicacy, the purple sea urchin Paracentrotus lividus is the most exploited echinoid species in the Mediterranean Sea, with a significant increase in total catches being reported over the last 2 decades. This work presents: (i) the findings from two demographic monitoring campaigns, conducted on P. lividus populations in summer 2023, at shallow depths within the coastal areas of Sicily and Apulia; (ii) a meta-analysis of the P. lividus density in the Mediterranean Sea over the last 30 years. In both sampled areas, the recorded individual density was lower than ever, with an average value of 0.2 ind/m2. No significant difference in P. lividus density was detected between protected and non-protected areas. The observed rarity of the edible sea urchin is corroborated by a meta-regression analysis of data from 44 published articles over the period 1990–2020, showing that the decline of P. lividus populations in the Mediterranean Sea began in 2003, coincident with the occurrence of a pan-European heat wave and with the anomalous warming of the entire Mediterranean Sea.